2020
DOI: 10.1111/jerd.12613
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various antioxidants on micro‐shear bond strength of resin composite to bleached enamel

Abstract: Objective: Teeth bleaching causes an immediate decrease in resin composite bonding ability. This study aimed to investigate the influence of various antioxidants on resin composite bond strength to bleached enamel. Materials and methods: One hundred and ten human maxillary incisors were used. A negative control (group A) (n = 10) was assigned (no bleaching-no antioxidant). The remaining teeth were divided into two groups (n = 50) according to the bleaching agent used: group B (40% hydrogen peroxide) and group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…Our findings demonstrated that the application of 10 % SA immediately after bleaching, allowed the adhesive procedure to provide a hybrid layer similar to the NB group. This finding suggests that similar the occurrence in bleached enamel, SA is effective in eliminating peroxide free radicals, allowing faster polymerization of adhesive materials without any premature interruption (Briso et al, 2012;Thapa et al, 2013;Briso et al, 2014;Kavitha et al, 2016;Elawsya et al). However, no differences in the hybrid layer formation were observed between the 38HP-AT and 38HP groups, demonstrating that AT did not have significant effects in reversing the effect of the bleaching procedure on the hybrid layer formation (Thapa et al).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings demonstrated that the application of 10 % SA immediately after bleaching, allowed the adhesive procedure to provide a hybrid layer similar to the NB group. This finding suggests that similar the occurrence in bleached enamel, SA is effective in eliminating peroxide free radicals, allowing faster polymerization of adhesive materials without any premature interruption (Briso et al, 2012;Thapa et al, 2013;Briso et al, 2014;Kavitha et al, 2016;Elawsya et al). However, no differences in the hybrid layer formation were observed between the 38HP-AT and 38HP groups, demonstrating that AT did not have significant effects in reversing the effect of the bleaching procedure on the hybrid layer formation (Thapa et al).…”
Section: Discussionmentioning
confidence: 92%
“…Dental bleaching is one of the non-invasive procedures that meets the public demand for cosmetic dentistry (Carey, 2014). During bleaching, free radicals formed by the interaction of bleaching agent with the tooth structure, act by reducing the chromophore molecules and thus making them less pigmented (Elawsya et al, 2021). In some cases, where the color changes have not sufficiently resolved with bleaching or there is a significant loss of tooth structure, restorative procedures are necessary on the whitened structure (Cavalli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery new antioxidant as an active agent for teeth whitening is an important research target in exploring new bioactive compound from medicinal plants, and recently in dentistry, the antioxidant agent is used to decrease bond strength after bleaching. [ 16 ] Many plants were reported as source of antioxidant agents with a function to prevent any free radical reaction in our body. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The sample size (n = 14) was estimated based on a previous study that evaluated the effect of the application of different antioxidant substances on shear bond strength to bleached enamel. Taking into account a comparative study design with 6 groups, a minimum detectable difference of 5.1 in the means, a standard deviation of 3.6, power of 0.8 and α = 0.05 26 .…”
Section: Specimen Preparation and Bleaching Proceduresmentioning
confidence: 99%
“…To overcome this, different methods have been proposed, like the use of alcohol for treating bleached enamel, application of adhesives containing organic solvents, removal of the external enamel layer, and use of synthetic or natural antioxidant agents 3,5,8,9,13,[22][23][24][25] . Sodium ascorbate, green tea extract, grape seed extract, and pomegranate peel extract are some antioxidants that can effectively improve bonding to bleached enamel 26 . The last ones, have the potential to neutralize free radicals and to interfere with their formation 18,23 .…”
Section: Introductionmentioning
confidence: 99%